A PHILOSOPHICAL COMPARISON OF THE AESTHETICS OF FRENCH NOUVELLE CUISINE AND KAISEKI CUISINE - Wong, Lok Io (2025)
This dissertation conducts a comparison of French Nouvelle Cuisine and Japanese Kaiseki Cuisine, exploring the similarities and differences of both cuisines and reflecting how cultural values, philosophical aspects, and historical influences have shaped contemporary dining experiences. In the examination of both cuisines, it takes into consideration aspects such as sensory experience, plating, and their underlying philosophical principles to demonstrate the interaction between aesthetics and culture particularly in relation to the culinary arts. French nouvelle cuisine was influenced by the Enlightenment, and this type of Western cuisine highlights a focus on texture and balance in flavor, emphasizing freshness, innovation, and intellectual artistry. Kaiseki cuisine inherited the tradition of the Japanese tea ceremony and is essentially rooted in Zen Buddhism. Some of the core aesthetic concepts in Kaiseki cuisine include seasonality, simplicity, and the aesthetic concept of wabi-sabi, emphasizing how humans should live in harmony with nature. As these two types of cuisines are compared, there will also be a comparison of Immanuel Kant’s aesthetics and how it is related to French nouvelle cuisine, as representative of a Western philosophical view and this will be compared to Japanese aesthetics in general and, in particular, the views on aesthetics of the Japanese philosopher Daisetsu Teitaro Suzuki, as representative of an Eastern philosophical view and its relation to culinary arts.